Mechanisms of epigenetic and cell-type specific regulation of Hey target genes in ES cells and cardiomyocytes. (February 2015) - Weber, David; Heisig, Julia; Kneitz, Susanne; Wolf, Elmar; Eilers, Martin; Gessler, Manfred
Abstract: Hey bHLH transcription factors are critical effectors of Notch signaling. During mammalian heart development they are expressed in atrial and ventricular cardiomyocytes and in the developing endocardium. Hey knockout mice suffer from lethal cardiac defects, such as ventricular septum defects, valve defects and cardiomyopathy. Despite this functional relevance, little is known about the regulation of downstream targets in relevant cell types. The objective of this study was to elucidate the regulatory mechanisms by which Hey proteins affect gene expression in a cell type specific manner. We used an in vitro cardiomyocyte differentiation system with inducible Hey1 or Hey2 expression to study target gene regulation in cardiomyocytes (CM) generated from murine embryonic stem cells (ESC). The effects of Hey1 and Hey2 are largely redundant, but cell type specific. The number of regulated genes is comparable between ESC and CM, but the total number of binding sites is much higher, especially in ESC, targeting mainly genes involved in transcriptional regulation and developmental processes. Repression by Hey proteins generally correlates with the extent of Hey-binding to target promoters, Hdac recruitment and lower histone acetylation. Functionally, treatment with the Hdac inhibitor TSA abolished Hey target gene regulation. However, in CM the repressive effect of Hey-binding is lost for a subset of genes. These also lack Hey-dependent histone deacetylation in CM and are enriched for binding sites of cardiac specific activators like Srf, Nkx2-5, and Gata4. Ectopic Nkx2-5 overexpression in ESC blocks Hey-mediated repression of these genes. Thus, Hey proteins mechanistically repress target genes via Hdac recruitment and histone deacetylation. In CM Hey-repression is counteracted by cardiac activators, which recruit histone acetylases and prevent Hey mediated deacetylation and subsequent repression for a subset of genes. Highlights: Cell type specific Hey target regulation in embryonic stem cells and cardiomyocytes Repression is linked to promoter binding, Hdac recruitment and histone deacetylation. Hdac inhibition by Trichostatin A prevents Hey-mediated repression. Cardiac activators (e.g. Nkx2-5) counteract Hey-mediated repression in cardiomyocytes.